1999
DOI: 10.1128/jcm.37.9.2777-2780.1999
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reference Standard Sensitivity on Accuracy of Rapid Antigen Detection Assays and a Leukocyte Esterase Dipstick for Diagnosis of Chlamydia trachomatis Infection in First-Void Urine Specimens from Men

Abstract: A total of 128 previously frozen first-void urine (FVU) specimens from selected asymptomatic men were centrifuged and tested by threeChlamydia trachomatis rapid antigen detection tests and with a leukocyte esterase (LE) dipstick. When the results were compared to those of a reference standard of positivity determined by the Chlamydiazyme enzyme immunoassay as confirmed by a blocking assay, the sensitivities of the Testpack Chlamydia (Abbott), Clearview Chlamydia (Unipath), and Surecell Chlamydia (Kodak) tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…Three studies reported results for the CRT against a NAAT (PCR), 50,65,72 and a further eight reported results 64,[66][67][68][69][70][71]73 for other POCTs, either still available on the market (as confirmed by their respective manufacturers) or possibly still available on the market (where no confirmation had been received from the manufacturer regarding whether or not the test was still available). In addition, reports of two unpublished studies were provided for this review by the Diagnostics Development Unit at the University of Cambridge, under the condition that they be treated as academic-in-confidence.…”
Section: Chaptermentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported results for the CRT against a NAAT (PCR), 50,65,72 and a further eight reported results 64,[66][67][68][69][70][71]73 for other POCTs, either still available on the market (as confirmed by their respective manufacturers) or possibly still available on the market (where no confirmation had been received from the manufacturer regarding whether or not the test was still available). In addition, reports of two unpublished studies were provided for this review by the Diagnostics Development Unit at the University of Cambridge, under the condition that they be treated as academic-in-confidence.…”
Section: Chaptermentioning
confidence: 99%
“…Table 4 shows summary information for the 13 studies reporting diagnostic accuracy outcomes. 50,[64][65][66][67][68][69][70][71][72][73][74][75] Nine studies 50,64,65,[68][69][70]72,74,75 involving 5914 participants provided details of when they took place, with an earliest start date of September 1996 and a latest end date of May 2008. However, it should be noted that one study 71 was published before the earliest specified start date, although it did not actually report details of when the study took place.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Urine LE testing can be used to diagnose urethritis but cannot distinguish the infecting organism (Black, 1997;Bowden, 1998). Although the CDC includes a positive LE dipstick test in their diagnostic criteria for urethritis, many authorities recommend reserving this test for screening asymptomatic males to determine who should receive further diagnostic testing (Black, 1997;Bowden 1998;Chernesky, Jang, Krepel, Sellors, & Mahony, 1999).…”
Section: Evaluation and Managementmentioning
confidence: 99%
“…Until then, there is some evidence that urine LE dipstick screening of asymptomatic males can be effective. In a study of 128 asymptomatic males, (Chernesky et al, 1999) results of the LE dipstick of first-voided urine specimens compared with 3 rapid antigen tests and with LCR demonstrated that the LE dipstick was the most sensitive indicator of chlamydia infection. Urine dipstick testing is easily performed and extremely cost effective; however, it is not specific for any cause of urethritis (Black, 1997;Bowden, 1998).…”
Section: Screening Asymptomatic Adolescent Malesmentioning
confidence: 99%
See 1 more Smart Citation